How the rhinoceros got his skin - Kelly, Miles; Parton, Daron (United Kingdom : Miles Kelly Publishing, 2018)
Rudyard Kipling's brilliantly funny tale of How the Rhinoceros got his Skin has been perfectly captured by Daron Parton's quirky and colourful illustrations. Every page showcases delightful full-bled artwork, packed with charm and detail that will enthrall. The story has been simply retold to appeal to young readers and listeners alike.
Primary
800-899
Keywords: Children's stories; Rhinoceros -- Juvenile fiction; Jungles -- Juvenile fiction